Implementasi Sistem Pendukung Keputusan Prioritas Pengaduan Warga Menggunakan Metode TOPSIS - Guruh Aji Saputra; Nurhasanah (CV. Multi Kreasi Media, 2026)
Prioritizing residents' complaints is an essential aspect of improving the effectiveness of residential community management. At De Fatmawati Housing Estate, the prioritization process is still performed manually, making it difficult for administrators to determine which complaints should be addressed first when multiple reports are submitted simultaneously. This study implements a web-based Decision Support System (DSS) by applying the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to support a more objective complaint prioritization process. The system was developed using the Agile Development methodology, while research data were collected through observation, interviews, and literature review. Complaint prioritization was conducted based on six evaluation criteria: urgency level, impact, complaint frequency, resource availability, handling cost, and complaint submission time. The implementation results demonstrate that the proposed system is capable of generating complaint priority rankings based on TOPSIS preference values, thereby supporting a more objective, transparent, and efficient decision-making process. Furthermore, the system provides an effective approach to addressing challenges in complaint prioritization while improving the overall effectiveness of complaint management within the residential community